Exploring Cancer Epidemiology and Associated Risk Factors in Chattogram, BangladeshBackground: The prevalence of various cancers is rising steadily in our country. To tackle the catastrophe of cancer related disease burden, identifying individuals at risk - Akter, Sanjina; Pasha, Md Ridoan; Alam, Mohammad Rashedul (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: The prevalence of various cancers is rising steadily in our country. To tackle the catastrophe of cancer related disease burden, identifying individuals at risk is essential. The objectives of this study were to investigate the sociodemographic features of cancer patients as well as to explore the probable risk factors to organize targeted awareness campaigns. Materials and methods: This cross-sectional study was conducted among 200 patients attending the Oncology Outpatient Departments of the two largest tertiary care hospitals of Chattogram division from September 2022 to October 2022. Data was collected by face-to-face interview with a semi-structured pretested questionnaire and patients’ record, and analyzed by SPSS Version 23.0 and STATA/IC1. Chi-squared test was used to analyze qualitative data and p-value was considered significant if it was <0.05 at 95% level of confidence. Results: Cancer was most prevalent (44%) among the age group of 41-60 yrs. In women the most prevalent type of cancer was breast cancer (33.93%) followed by cervical cancer (13.39%), and ovarian cancer (9.93%) while in men the most prevalent cancer was lung cancer (29.55%). Patients taking contraceptives had a significantly increased risk of suffering from breast cancer and cervical cancer (p<0.05). Highly significant association of smoking with lung cancer (p<0.01), laryngeal cancer (p<0.01) head-neck cancer (p<0.01) and esophagus cancer (p<0.05) were revealed from this study. Conclusion: Significant differences in cancer types and risk factors between various demographic groups are highlighted by the study. These highlights the necessity for focused cancer preventive initiatives, such as improved regional public awareness campaigns, educating on modifiable risk factors, and early detection programs. JCMCTA 2024 ; 35 (2) : 124-129